Bronze Age and other surface finds from Bratonci in the Prekmurje region, Slovenia - Guštin, Mitja; Zorko, Monika (Arheološki vestnik, 2013)
The first artefacts on the fields south of the village of Bratonci, Slovenia, came to light roughly a decade ago. The existence of an archaeological site there has since been confirmed by over 1500 archaeological finds, predominantly pottery. The finds mostly date to the Early and Middle Bronze Ages, also the transition to the Late Bronze Age, and indicate a settlement. A small number of recovered finds dates to later periods, from the Early Iron Age to modern times.